2008
DOI: 10.1021/nl0732171
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Energetic Levels in Nanocrystal Quantum Dots through Surface Manipulations

Abstract: We demonstrate tuning of the electronic level positions with respect to the vacuum level in colloidal InAs nanocrystals using surface ligand exchange. Electrochemical as well as scanning tunneling spectroscopy measurements reveal that the tuning is largely dependent on the nanocrystal size and the surface linking group, while the polarity of the ligand molecules has a lesser effect. The implications of affecting the electronic system of nanocrystal through its capping are illustrated through prototype devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
197
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 172 publications
(203 citation statements)
references
References 33 publications
3
197
1
2
Order By: Relevance
“…Similar results have been reported for CdSe and InAs nanoparticles with VBM shifts of as much as 0.4 eV depending on the ligand. 60,61,63 In the case of CdSe, it was suggested that these differences may be explained by the degree of hole scavenging and surface passivation. A ligand with suitable trap sites for holes or poor binding affinity and incomplete surface site passivation (thiols, pyridine) was found to induce a lower VBM position than ligands without these properties (primary amines in the case of CdSe).…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…Similar results have been reported for CdSe and InAs nanoparticles with VBM shifts of as much as 0.4 eV depending on the ligand. 60,61,63 In the case of CdSe, it was suggested that these differences may be explained by the degree of hole scavenging and surface passivation. A ligand with suitable trap sites for holes or poor binding affinity and incomplete surface site passivation (thiols, pyridine) was found to induce a lower VBM position than ligands without these properties (primary amines in the case of CdSe).…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…These processes increase the device conductance by decreasing the distance between neighboring NCs and therefore reducing the inter-particle tunneling barrier. In some cases, certain ligands donate charge [16,17] and in other cases the NCs energy levels may be modified through ligand exchange chemistry [18][19][20].…”
mentioning
confidence: 99%
“…These tunable properties have been implemented in nanocrystal (NC) based devices made of a single component, 1,2 as a combination of different nanocrystals or compositions, 3 or in hybrid organic-inorganic devices where nanocrystals were interfaced with semiconducting polymers. [4][5][6][7][8][9][10] Despite the progress made in many aspects of nanocrystal's synthesis and devices made of them, there seems to remain an issue that holds back some applications. There are many reports that although the photoluminescence (PL) efficiency of near infrared (NIR) emitting NCs in solution could be 20% or above, the quantum efficiency (QE) measured for solid films is in the range of 1% and often below it.…”
mentioning
confidence: 99%